Uso da Técnica STU para Avaliação do Desempenho de Bibliotecas Intervalares - Sagula, Rafael Linden; Diverio, Tiarajú Asmuz; Netto, João Cesar (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1998)
In this paper, we present the STU (Standard Time Unit) technique, which is used with performance avaluation of interval software packages. Comparisons were done using a classic aproach to benchmarks and the results have been showed. lnterval libraries are evaluated using the STU method and the obtained results right the problems caused by the usage of different environments.